Photoredox halogenation of quinolones: the dual role of halo-fluorescein dyes. Issue 20 (6th May 2021) - Ritu,; Kumar, Sharvan; Chauhan, Parul; Jain, Nidhi
Abstract : An unprecedented visible light mediated regioselective C-3 halogenation of quinolones was achieved using halo-fluorescein dyes as a halogen source and air as an oxidant. This reaction has broad substrate scope and gives 3-halo quinolone derivatives. Abstract : An efficient C-3 halogenation of quinolin-4-ones is reported with halogenated fluorescein dyes which serve both as a halogen source and photocatalyst. This reaction shows broad substrate scope and gives good to excellent yields of C-3 brominated/iodinated quinolones with eosin Y/rose bengal in green light under ambient conditions. The mechanistic investigations suggest a radical pathway involving the oxidative dehalogenation of the dye in the presence of air.